2018
DOI: 10.1177/0033294118786688
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Effects of Acute Exercise on Episodic Memory Function: Considerations for the Timing of Exercise

Abstract: Our previous work employing a between-subject randomized controlled trial design suggests that exercising prior to memory encoding is more advantageous in enhancing retrospective episodic memory function when compared to exercise occurring during or after memory encoding. The present experiment evaluates this potential temporal effect of acute exercise on memory function while employing a within-subject, counterbalanced design. In a counterbalanced order (via Latin squares), 24 participants completed four visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 22 publications
6
49
0
Order By: Relevance
“…Additionally, and similar to other studies [33][34][35][36], participants were excluded if they: Self-reported as a daily smoker [37,38] Self-reported being pregnant [39] Exercised within 5 hours of testing [40] Consumed caffeine within 3 hours of testing [41] Had a concussion or head trauma within the past 30 days [42] Took marijuana or other illegal drugs within the past 30 days [43] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [44]…”
Section: Participantssupporting
confidence: 91%
“…Additionally, and similar to other studies [33][34][35][36], participants were excluded if they: Self-reported as a daily smoker [37,38] Self-reported being pregnant [39] Exercised within 5 hours of testing [40] Consumed caffeine within 3 hours of testing [41] Had a concussion or head trauma within the past 30 days [42] Took marijuana or other illegal drugs within the past 30 days [43] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [44]…”
Section: Participantssupporting
confidence: 91%
“…The present study, written as a brief report, aimed to evaluate whether acute exercise can enhance a cognitive-related reversal learning effect. The motivation for this experimentation came from past work demonstrating that acute exercise can enhance the functional connectivity of neurons [32], improve cognitive flexibility [15][16][17], as well as improve memory function [1][2][3][4][5][6][7], all of which are important for cognitive-related learning. In the present experiment, our main findings were as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research demonstrates that acute exercise is associated with enhanced memory performance [1][2][3][4][5][6][7]. Mechanisms of this potential effect are multifold, including, for example, exercise-induced neuronal excitability, transcription factor expression, and growth factor production [8].…”
Section: Introductionmentioning
confidence: 99%
“…In alignment with other related experiments [1][2][3][4][5][6], 20 participants were randomized into both groups (N=40). Recruitment occurred via a convenience-based, non-probability sampling approach (classroom announcement and word-of-mouth).…”
Section: Participantsmentioning
confidence: 99%
“…Of interest to our group is the effects of exercise on memory function, including both episodic memory (recall of past events) and semantic memory (recall of past information not bound to a particular event). Acute exercise has been shown to enhance episodic memory function, particularly the short-term recall of recently encoded information (e.g., word list) [1][2][3][4][5][6]. Mechanisms of such an effect have been detailed elsewhere [7][8][9][10], and include, for example, exercise-induced alterations in neuronal excitability and priming (e.g., via CREB [cAMP response element binding] phosphorylation) neuronal networks for engram trace development.…”
Section: Introductionmentioning
confidence: 99%